2012
DOI: 10.1002/jbmr.1546
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of FGF23 processing in fibrous dysplasia

Abstract: Fibroblast growth factor-23 (FGF23) is a phosphate-and vitamin D-regulating hormone derived from osteoblasts/osteocytes that circulates in both active (intact, iFGF23) and inactive (C-terminal, cFGF23) forms. O-glycosylation by O-glycosyl transferase Nacetylgalactosaminyltransferase 3 (ppGalNAcT3) and differential cleavage by furin have been shown to be involved in regulating the ratio of active to inactive FGF23. Elevated iFGF23 levels are observed in a number of hypophosphatemic disorders, such as X-linked, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 36 publications
(37 reference statements)
3
73
0
Order By: Relevance
“…The mechanisms by which Fam20C is functionally or expressionally regulated are unknown. Recent studies examining the production of intact and/ or C-terminal fragments of FGF23 in fibrous dysplasia and during physiological situations of low iron, such as in ADHR (36,37), support that GalNAc-T3 and furin are likely controlled by multiple factors including 3′,5′-cyclic adenosine monophosphate (38), iron or iron deficiency (39), and inorganic phosphate (40).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which Fam20C is functionally or expressionally regulated are unknown. Recent studies examining the production of intact and/ or C-terminal fragments of FGF23 in fibrous dysplasia and during physiological situations of low iron, such as in ADHR (36,37), support that GalNAc-T3 and furin are likely controlled by multiple factors including 3′,5′-cyclic adenosine monophosphate (38), iron or iron deficiency (39), and inorganic phosphate (40).…”
Section: Discussionmentioning
confidence: 99%
“…Further confirmation came from the discovery that elevated levels of FGF23 were responsible for tumor-induced osteomalacia (TIO) [6,7]. In rapid succession, FGF23 was implicated in other phosphatewasting syndromes including autosomal recessive h y p o p h o s p h a t e m i c r i c k e t s [ 8 -1 2 ] , X -l i n k e d hypophosphatemic rickets [13], and fibrous dysplasia [14,15]. There are currently at least 11 disorders of altered phosphate homeostasis associated with alternations in FGF23 physiology that have been well characterized (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…117 Significantly, Bhattacharyya et al recently reported higher ratios of cFGF23 to iFGF23 in patients with FD compared to healthy controls (mean 1.7 vs. 0.99). 98 The authors also provided primary evidence of modified FGF23 processing from analysis of bone marrow stromal cells harbouring the causative activating G s a mutation (affecting the a-subunit of the stimulatory G-protein), which showed a cAMP-dependent inhibition of GALNT3 activity and increased furin activity. Conversely, cFGF23 to iFGF23 ratios in patients with renal failure were highly variable, ranging from $0.1 to $4 RU/pg.…”
Section: Accuracy and Reproducibility Of Methods For Fgf23 Measurementmentioning
confidence: 99%